Hukum Adat dan Ketahanan Pangan : Kearifan Lokal dalam Sistem Pertanian Tradisional - Arief Fahmi Lubis (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2022)
These traditional agricultural systems have proven effective in maintaining local food security for centuries, they now face various challenges. Pressures from population growth, land-use change, and climate change threaten the sustainability of many traditional agricultural systems. The purpose of this study is to show that the integration of local wisdom in the modern agricultural system has also begun to receive recognition in national policies. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that with the right approach, recognition and protection of customary rights can be an important foundation in building a food security system that is not only productive, but also ecologically sustainable and socially just.